Modeling of capital budget for the estabilishment of new food and beverage logistic company: case study in jabodetabek area (2019 - 2028) - Kanyaka Ananggadipa, Vanya; M. Daryanto, Wiwiek (The Indonesian Journal of Business Administration, 2019)
Abstract – Indonesia is the third most populous country in Asia with estimated population of 266 million people in 2018. It becomes the largest market for the food service industry in the ASEAN. Here, the trend of eating out in such restaurants has become part of social activities. The research revealed that 11% of Indonesians eat out in restaurant at least once a day. The growth outlook for food franchises in Indonesia also look good accordingly. However, one of the key to success for the food company is their logistic operations, which is no easy task in the Indonesian environment as an archipelago. Driven by those situation, PT ABC as a leader in Indonesia food industry have decided to establish an independent logistic company named PT DEF. Therefore, the purpose of this study is to assess the economic aspect of the new logistic company to independently operate based on financial terms using capital budgeting model for 10 years’ period in Jabodetabek. The study starts to define the capital structure and Weighted Average Cost of Capital, and Capital Budgeting indicators. The findings show that the capital budgeting indicators is better with 50:50 composition of debt and equity which results the IRR at 68.02% where greater than WACC at 11.13%. The investment generates the NPV of IDR 19.401.050.397, the PI at 8.0, and the payback period is within 3.5 years. This investment also expected to get 17.92% ROI at the first year. So financially the company is considered feasible to be established. The author believe that the findings will be beneficial for the management to come up the best solution for their financing proportion and generate more profit. Keywords: capital budgeting model, capital structure, food logistic industry, financial feasibility study